P3. 13-15 First-Line Afatinib Dose Initiation and Adjustment in Patients with EGFR Mutant Advanced Non-Small Cell Lung Cancer - Chai, Chee Shee; Liam, Chong Kin; Ho, G.; A., Binti Alip; Pang, Y. (Elsevier, 2018)
Background: The recommended starting dose of afatinib is 40mg od with 20mg, 30mg and 50mg tablets available for dose adjustment.